2020
DOI: 10.1177/1556984520920724
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Conversion and Adverse Intraoperative Events in Robotically Enhanced Minimally Invasive Coronary Artery Revascularization

Abstract: Objective The transition from sternotomy access to minimally invasive coronary artery bypass grafting is associated with steep learning curves. This study reports the reasons for sternotomy conversions from robotically enhanced minimally invasive direct coronary artery bypass grafting (RE-MIDCAB) and describes potential risk reduction strategies. Methods The perioperative data of 759 RE-MIDCAB patients (me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…When not performed as the primary operation, multiple studies have shown that MIDCAB can be performed in cases of reoperation. [ 94 99 ] As opposed to CABG reoperations, MIDCAB has proven to be more effective and not linked to increased mortality and morbidity. [ 100 , 101 ] MIDCAB is also a viable alternative to CABG and can also replace PCI in patients for whom PCI is either risky or impossible.…”
Section: Discussionmentioning
confidence: 99%
“…When not performed as the primary operation, multiple studies have shown that MIDCAB can be performed in cases of reoperation. [ 94 99 ] As opposed to CABG reoperations, MIDCAB has proven to be more effective and not linked to increased mortality and morbidity. [ 100 , 101 ] MIDCAB is also a viable alternative to CABG and can also replace PCI in patients for whom PCI is either risky or impossible.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 , 9 - 11 ] Similar to the results of Christidis et al,[ 9 ] the most common cause of conversion was intramyocardial LAD in our study. In contrast, van der Merwe et al[ 10 ] showed that the most common causes of conversion were lung adhesions (36.7%) and LIMA dysfunction (36.7%). The main finding of our study is that older age is the only univariate risk factor for conversion.…”
Section: Discussionmentioning
confidence: 94%
“…A conversion that occurred in the very beginning during the docking period or access to hemithorax was classified as early conversion, while conversion which occurred after safe access was achieved was classified as later conversion. The reasons for conversion were lung adhesion 11 (36.7%), inadequate lung isolation 1 (3.3%), ITA dysfunction 11 (36.7%), poor target vessel visualization 3 (10%), and ventricular perforation, arrhythmia, acute heart failure, and anastomosis dysfunction 1 (3.3%) each [ 26 ]. We also had one LIMA damage in the RACAB group but harvesting in that case was fully completed.…”
Section: Discussionmentioning
confidence: 99%